Comparison of Delayed and Immediate Mandibular Molar Implant Placement by Use of Resonance Frequency Analysis: Three Year Study - Hina Jabeen, Tariq Sardar, Mohammad Umar, Umer Ullah, Syed Wahib Asif Zaidi, Raja Muhammad Daniyal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: In order to replace a lost mandibular 1st molar, the objective was to assess & associate the clinical results of delayed & immediate packing of implant-supported prostheses. The assessment was conducted utilizing the following observations: implant mobility, peri-implant radiolucency, probing depth, marginal bone level, & bleeding on probing. Methodology: Thirty participants who in necessity of an implant-sustained prosthesis for a lost lower 1st molar, had good oral hygiene, & were keen to follow the research protocol were involved in the three-year trial beginning in December 2019. Results: With a mean age of 23.1 years & a range of 19 - 31 years, the research included 15 patients, 75% men & 25% women. Implants in Group 1 varied in diameter from 3.6 - 4.7 mm, with a mean of 4.44 mm, whereas implants in Group2 ranged in diameter from 3.2 - 4.1 mm, with a mean of 4.00 mm. Implants in Groups 1 & 2 had a length that varied from 10 - 14 mm, with a mean of 12 mm. Conclusion: An effective treatment option & an alternate to the outdated late loading is the single tooth implant restoration in the lower 1st molar with quick loading. Immediate loading decreases the functional treatment time delay. It eliminates patient discomfort & offers a permanent prosthesis with immediate functionality.